2021
DOI: 10.1007/s10111-020-00663-8
|View full text |Cite|
|
Sign up to set email alerts
|

The influence of training level on manual flight in connection to performance, scan pattern, and task load

Abstract: This work focuses on the analysis of pilots’ performance during manual flight operations in different stages of training and their influence on gaze strategy. The secure and safe operation of air traffic is highly dependent on the individual performances of the pilots. Before becoming a pilot, he/she has to acquire a broad set of skills by training to pass all the necessary qualification and licensing standards. A basic skill for every pilot is manual control operations, which is a closed-loop control process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
(37 reference statements)
1
2
0
Order By: Relevance
“…When evaluating the relationship between humans and equipment through eye-tracking devices, eye movement data were used to analyse human behaviours. This hypothesis was confirmed by many previous researchers [14], such as mental fatigue [15], cognitive load [16], information acquisition [17], situational awareness [18], scanning behaviours [19], attention [20], physiological measurements [21], workload [22, 23], interface evaluation and human-computer interaction [24, 25]. Research on eye movement data that predicted pilots’ behaviour included how different role assignments influenced decisions in high-risk environments, and how to predict pilots’ decisions by paying attention to relevant information about pilots’ choices [26].…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…When evaluating the relationship between humans and equipment through eye-tracking devices, eye movement data were used to analyse human behaviours. This hypothesis was confirmed by many previous researchers [14], such as mental fatigue [15], cognitive load [16], information acquisition [17], situational awareness [18], scanning behaviours [19], attention [20], physiological measurements [21], workload [22, 23], interface evaluation and human-computer interaction [24, 25]. Research on eye movement data that predicted pilots’ behaviour included how different role assignments influenced decisions in high-risk environments, and how to predict pilots’ decisions by paying attention to relevant information about pilots’ choices [26].…”
Section: Introductionsupporting
confidence: 78%
“…scanning behaviours [19], attention [20], physiological measurements [21], workload [22,23], interface evaluation and human-computer interaction [24,25].Research on eye movement data that predicted pilots' behaviour included how different role assignments influenced decisions in high-risk environments, and how to predict pilots' decisions by paying attention to relevant information about pilots' choices [26]. When using eye movement to predict dangerous situations, Francisco [27] found that saccade, gaze, blink and gaze dispersion in horizontal and vertical dimensions in eye movement features were more likely to predict the occurrence of dangerous situations.…”
Section: Application Of Eye Movement Datamentioning
confidence: 99%
“…The increase in task complexity can easily lead to the decline of novice pilots' information perception and rapid response, making novice pilot exposed to SA deterioration and safety risk growth [ 53 , 54 ]. Researchers are trying to develop various training methods [ 55 , 56 ], including optimizing pilot's visual attention mode [ 57 , 58 ], promoting pilot's mental state [ 59 , 60 ], enhancing aircrew communication and cooperation [ 33 ], etc. The training methods can help novice pilot to maintain the abilities of efficient perception, appropriate decision-making, and dynamic adaptation stably, thus ensuring optimal performance and flight safety [ 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%